Simulation of a flow over a mound-type breakwater of different surface roughness using computational approach / Muhammad Hafiz Haikal Azahar - Azahar, Muhammad Hafiz Haikal (2022)
Wave run-up over coastal structures and breakwaters is one of the most important hydraulic reactions used in crest elevation of designs for coastal structures. The design of rubble mound breakwaters is typically based on an empirical formula and physical modeling. The challenges are typically due to the challenges are typically normally lower. The general problems with physical models of coastal structure tests are costly and time-consuming. However, from all problems state in the experiment before there are several problems which are high cost, take more time to build, and use complex formulas for surface roughness mound breakwater. The objectives are to investigate integration between a traditional rubble mound breakwater and a reservoir to store the wave overtopping from the incoming wave to extract energy. To determine the relative difference in overtopping behavior for various types of armor units leading to roughness factors γf for the database and for use in the neural network prediction of overtopping.